2001
DOI: 10.1002/jcb.1211
|View full text |Cite
|
Sign up to set email alerts
|

ERK 1,2 and p38 pathways are involved in the proliferative stimuli mediated by urokinase in osteoblastic SaOS‐2 cell line

Abstract: Bone metastases from prostate origin generate an osteoblastic reaction that is expressed in vitro by increased osteoblast proliferation. The urokinase-like plasminogen activator (u-PA) present in the media conditioned by tumoral prostatic cells acting as a ligand of the cellular membrane receptor (u-PAR), has been identified as the specific factor that modulates this proliferative reaction. The present study represents an effort to unravel the intracellular pathway by which u-PA activates osteoblastic prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…DUSP26 can dephosphorylate both p38 and ERK in ATC cells, but it is more effective at inactivating p38. ERK is thought to be involved in cell proliferation (Widmann et al, 1999), whereas p38 participates in the regulation of apoptosis (Bulavin and Fornace, 2004a), although it has been shown that p38-MAPK cascades enhance survival (Liu et al, 2001;Park et al, 2002), cell growth (Juretic et al, 2001) and differentiation (Yosimichi et al, 2001). Many effectors can alter the balance between ERK and p38, and such changes could have profound consequences for tumor growth and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DUSP26 can dephosphorylate both p38 and ERK in ATC cells, but it is more effective at inactivating p38. ERK is thought to be involved in cell proliferation (Widmann et al, 1999), whereas p38 participates in the regulation of apoptosis (Bulavin and Fornace, 2004a), although it has been shown that p38-MAPK cascades enhance survival (Liu et al, 2001;Park et al, 2002), cell growth (Juretic et al, 2001) and differentiation (Yosimichi et al, 2001). Many effectors can alter the balance between ERK and p38, and such changes could have profound consequences for tumor growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…ERK is thought to be involved in cell proliferation (Widmann et al, 1999). On the other hand, a recent study highlighted p38 as a negative regulator of cellcycle progression along with its previously well-characterized proapoptotic functions (Bulavin and Fornace, 2004a), although it has been shown that p38-MAPK cascades enhance survival (Liu et al, 2001;Park et al, 2002), cell growth (Juretic et al, 2001) and differentiation (Yosimichi et al, 2001). The coordinated balance between ERK and p38 activity may represent a critical mechanism for controlling cell-fate decisions as well (McMullen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additional mechanisms resulting from decreased activity of MAPK pathways (p38 MAPK and ERK1/2) (Figures 4 and 10) may have also contributed to the DPI-induced G 1 checkpoint. While the role of ERK1/2 in proliferation is well established and works downstream of many stimuli, including growth factors and hormones (Yoon and Seger, 2006), p38 MAPK has often been associated with stress responses (Dent et al, 2003); however, p38 MAPK has also been shown to promote proliferation in a variety of cell types (Juretic et al, 2001;Frigo et al, 2006). Common (for example, c-jun, c-fos) and numerous distinct substrates have been identified as targets of ERK1/2 and p38 MAPK activity (Ono and Han, 2000;Yoon and Seger, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence for a role of p38 in the regulation of cyclin D1 protein ubiquitination and subsequent degradation through direct phosphorylation of a threonine residue (Casanovas et al, 2000). Furthermore, both positive (Crawley et al, 1997;Maher, 1999;Juretic et al, 2001;Recio and Merlino, 2002;Zhao et al, 2002) and negative (Diehl et al, 2000;Puri et al, 2000;Alderton et al, 2001;Smalley and Eisen, 2002) roles of p38 in cell proliferation have been described, suggesting that the mitogenic and antimitogenic functions of p38 are dependent on the cell type and possibly other factors.…”
mentioning
confidence: 99%